OPTING FOR THE TEACHING PROFESSION: VOCATION OR OPPORTUNITY - ADRIANA DENISA MANEA; CRISTIAN STAN (Studia Universitatis Babes-Bolyai, 2015)
ABSTRACT. Our research aimed to study the motivational and attitudinal spectrum of people who chose to be teachers after graduation and decided to attend the post-graduate training program for pursuing a teaching career. The main method of investigation was the survey based on the questionnaire. The items of the questionnaire included the current employment status of trainees, the determination of the decision to pursue a teaching career, the motivation behind this option, the time horizon in which they think they will practice as teachers, as well as the estimated level of professional satisfaction. The study highlights the need for early vocational counseling programs that should ease a correct option for the teaching profession.